2021
DOI: 10.1088/1755-1315/700/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Static Structural Analysis and Determination of Low-Cost Component Sizes of The Paper Pulper Machines

Abstract: Paper pulper machines a capacity of 83 litres/process must have a low-cost material, robust and safe to operate. Paper pulper machine components analysed are tubes, frames, helical screw shaft and the shaft holder. The method uses a static structural analysis to obtain von mises stress and displacement. Static structural analysis uses finite element analysis with the help of CATIA® Software. The safe component size and lowest cost (safety factor more than 2.5) were selected in this study. Calculation of costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The finite element method is a numerical method used to solve partial differential equations and integral equations [18]. FEM is one method for predicting or analyzing stresses and deformations caused by loads [19][20][21]. Ansys be used to conduct material strength analyses such as stress and safety factor.…”
Section: Methodsmentioning
confidence: 99%
“…The finite element method is a numerical method used to solve partial differential equations and integral equations [18]. FEM is one method for predicting or analyzing stresses and deformations caused by loads [19][20][21]. Ansys be used to conduct material strength analyses such as stress and safety factor.…”
Section: Methodsmentioning
confidence: 99%
“…FEM has evolved into an effective and widely used numerical approach for engineering analysis and design [5]. The study revealed that the smaller the size of the material, the smaller the value of the safety factor, and the cheaper the material costs when selecting the structural design of a machine based on FEM and assessment of material prices [6]. In addition, the structural strength of mechanical components is only tested under static loading not under thermal load.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the structural strength of mechanical components is only tested under static loading not under thermal load. Several finite element method studies [2][3][4][5][6][7][8][9][10][11][12] establish the stress and deformation values of the design. It is quite expensive to test the developed product directly in the laboratory since the mechanical form of the product must be verified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design results will be tested statically using software to determine the strength of the chassis design and the factor of safety. Before designing the chassis, several things must be considered as a design reference; here are some general considerations described by Dahlan [2], (1) Types of loads and stresses caused by loads, (2) Types of component movement, (3) Type of material, (4) Shape and size of components, (5) Ergonomics, (6) Safety of operation, (7) Cost.…”
Section: Introductionmentioning
confidence: 99%